1981
DOI: 10.1111/j.1467-8624.1981.tb03097.x
|View full text |Cite
|
Sign up to set email alerts
|

Social Factors Influencing Absenteeism due to Illness in Nursery School Children

Abstract: An archival study involving data for 204 children enrolled in a nursery school examined social and other factors related to absenteeism from school due to reported illness. Parents' ratings of the child's sociability prior to entering school were inversely related to absenteeism rate during the first year of school after statistically controlling for socioeconomic class, birth order, sex, the child's early health history, and family and sibling interaction patterns. Additional analyses based on a subset of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1996
1996
1996
1996

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…To avoid an interaction entirely, an individual may complain about his or her discomfort in social interactions or other obligations he or she already has, excuses viewed by some as socially acceptable (Snyder & Smith, 1986). For example, Pennebaker, Hendler, Durrett, and Richards (1981) found that nursery school children who were low in sociability (i.e., shy, aggressive, etc.) had higher rates of absenteeism than children high in sociability.…”
Section: Individual-difference Variables Moderating Complainingmentioning
confidence: 99%
See 2 more Smart Citations
“…To avoid an interaction entirely, an individual may complain about his or her discomfort in social interactions or other obligations he or she already has, excuses viewed by some as socially acceptable (Snyder & Smith, 1986). For example, Pennebaker, Hendler, Durrett, and Richards (1981) found that nursery school children who were low in sociability (i.e., shy, aggressive, etc.) had higher rates of absenteeism than children high in sociability.…”
Section: Individual-difference Variables Moderating Complainingmentioning
confidence: 99%
“…One explanation that they proposed for this finding was that attending school for unsociable children was an aversive experience from which they desired an escape. Complaining of illness may be one way for the unsociable child to avoid the situation (Pennebaker et al, 1981).…”
Section: Individual-difference Variables Moderating Complainingmentioning
confidence: 99%
See 1 more Smart Citation